The Nature and Clinical Significance of Preinjury Recall Bias Following Mild Traumatic Brain Injury. Issue 6 (November 2016) - Silverberg, Noah D.; Iverson, Grant L.; Brubacher, Jeffrey R.; Holland, Elizabeth; Hoshino, Lisa Casagrande; Aquino, Angela; Lange, Rael T.
Abstract : Objective: Patients with mild traumatic brain injury (MTBI) often underestimate their preinjury symptoms. This study aimed to clarify the mechanism underlying this recall bias and its contribution to MTBI outcome. Setting: Level I trauma center. Participants: Patients with uncomplicated MTBI ( N = 88) and orthopedic injury ( N = 67). Design: Prospective longitudinal. Main Measures: Current and retrospective ratings on the British Columbia Postconcussion Symptom Inventory, completed at 6 weeks and 1 year postinjury. Results: Preinjury symptom reporting was comparable across groups, static across time, and associated with compensation-seeking. High preinjury symptom reporting was related to high postinjury symptom reporting in the orthopedic injury group but less so in the MTBI group, indicating a stronger positive recall bias in highly symptomatic MTBI patients. Low preinjury symptom reporting was not a risk factor for poor MTBI outcome. Conclusion: The recall bias was stronger and more likely clinically significant in MTBI patients with high postinjury symptoms. Multiple mechanisms appear to contribute to recall bias after MTBI, including the reattribution of preexisting symptoms to MTBI as well as processes that are not specific to MTBI (eg, related to compensation-seeking).